2020
DOI: 10.1136/bcr-2020-236254
|View full text |Cite
|
Sign up to set email alerts
|

Massive bilateral stroke in a COVID-19 patient

Abstract: Coronavirus disease 2019 (COVID-19) is a novel infection of which we still have much to learn. Microvascular and macrovascular complications are increasingly recognised as being among the drivers of morbidity and mortality in patients with this condition. Here we present a case of a woman with COVID-19 who suffered massive and bilateral middle cerebral artery strokes, which presented as reduced consciousness several days into admission. Clinicians need to be aware of possible causes of reduced consciousness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…For example, delirium was not associated with specific neuroimaging findings: Helms et al (2020b) observed this symptom in people with WM damage, fronto-temporal hypoperfusion, stroke, and haematomas, while other patients with delirium had no MRI abnormalities at all (Paterson et al, 2020). Decline in, or loss of, consciousness was also reported in patients with right frontal ischaemia (Basi et al, 2020), right temporal haemorrhage (Sharifi-Razavi et al, 2020), lesions of the left midbrain (Fan et al, 2020) and of the left ventromedial prefrontal cortex (Muhammad et al, 2020), extensive right-sided (Fan et al, 2020) or left-sided lesions (Mohamed et al, 2020), diffuse WM lesions (McCuddy et al, 2020;Muccioli et al, 2020), diffuse cerebrovascular alterations (Pugin et al, 2020) and also in the absence of MRI abnormalities (Manganelli et al, 2020;Mohamud et al, 2020). Similarly, altered mental status was observed in patients with one lesion in the splenium (Sparr and Bieri, 2020), scattered WM lesions (Farhadian et al, 2020), and microbleeds (Fitsiori et al, 2020), in a case with haemorrhage in the right parieto-occipital territory (Franceschi et al, 2020), but in most cases alterations in mental state were not associated with any specific MRI finding (Radmanesh et al, 2020a,b).…”
Section: Cognitive Correlates Of Neuroimaging Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, delirium was not associated with specific neuroimaging findings: Helms et al (2020b) observed this symptom in people with WM damage, fronto-temporal hypoperfusion, stroke, and haematomas, while other patients with delirium had no MRI abnormalities at all (Paterson et al, 2020). Decline in, or loss of, consciousness was also reported in patients with right frontal ischaemia (Basi et al, 2020), right temporal haemorrhage (Sharifi-Razavi et al, 2020), lesions of the left midbrain (Fan et al, 2020) and of the left ventromedial prefrontal cortex (Muhammad et al, 2020), extensive right-sided (Fan et al, 2020) or left-sided lesions (Mohamed et al, 2020), diffuse WM lesions (McCuddy et al, 2020;Muccioli et al, 2020), diffuse cerebrovascular alterations (Pugin et al, 2020) and also in the absence of MRI abnormalities (Manganelli et al, 2020;Mohamud et al, 2020). Similarly, altered mental status was observed in patients with one lesion in the splenium (Sparr and Bieri, 2020), scattered WM lesions (Farhadian et al, 2020), and microbleeds (Fitsiori et al, 2020), in a case with haemorrhage in the right parieto-occipital territory (Franceschi et al, 2020), but in most cases alterations in mental state were not associated with any specific MRI finding (Radmanesh et al, 2020a,b).…”
Section: Cognitive Correlates Of Neuroimaging Findingsmentioning
confidence: 97%
“…A sixth patient showed numerous hyperintensities, leukoaraiosis in the right intraparietal sulcus and microhaemorrhages in the left centrum semiovale, thalamus, left cerebellum and left anterior temporal lobe (Jaunmuktane et al, 2020). A seventh patient presented with bilateral ischaemic-haemorrhagic infarctions affecting, above all, a large proportion of the left hemisphere from frontal to occipital regions (Mohamed et al, 2020). An eight patient had several ischaemic regions scattered across his white matter including the cerebellum, deep white matter and centri semiovale, with a concomitant lenticular haemorrhage (Hanafi et al, 2020).…”
Section: Mixed Ischaemia and Haemorrhage Patternmentioning
confidence: 99%
“…As a comparartor, data from 2009 study in Seoul prior to COVID 19 reported ischemic stroke complicating 0.04% to 0.06% of hospital admissions for all clinical presentations. Mohamed IZ et al [10] and this deserves special attention. Sensitivity of COVID-19 PCR by nasal swab is 70% and specificity is 90% and this is the reason that the test needs to be repeated in strongly suspected cases as was true in our case [11].…”
Section: Discussionmentioning
confidence: 89%
“…Although not completely understood, the plausible proposed mechanism of cerebrovascular disease in COVID-19 includes viral neurotropism, coagulopathy from systemic inflammation and cytokine storm, and endothelial dysfunction leading to angiopathic thrombosis. There have been a handful of cases linking COVID-19 to large vessel macrothrombosis and antiphospholipid syndrome [ 4 ]. We reported an even more unusual case that presented with multiple focal neurologic symptoms and was found to have watershed infarctions secondary to COVID-19 with only mild respiratory symptoms, and without typical vascular risk factors, PFO or arrhythmia, after excluding autoimmune diseases, hypercoagulability diseases, and vasculitis; this report highlights the importance of suspecting this devastating disease in an otherwise healthy young patient who presents with focal neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%